2017
DOI: 10.4067/s0717-95022017000100050
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Characterization of the Renal Arteries in the Pig: Comparative Analysis with the Human

Abstract: SUMMARY:In spite of its importance as an experimental model, information on the renal artery in pigs is scarce. The objective of this work was to determine the morphological characteristics of the renal artery (RA) and its branches in pigs. One hundred and twenty one (121) pairs of kidneys of pigs destined to slaughter by stunning were studied. The RA and its branches were perfused with polyester resin (Palatal 85 % t Styrene 15 %) and subjected to KOH infusion (potassium hydroxide) for total corrosion. Calibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
17
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(32 citation statements)
references
References 11 publications
13
17
2
Order By: Relevance
“… 16 in the following types: pattern Ia, with the division of the renal artery into cranial and caudal polar branches, which branch into anterior and posterior segmental branches; pattern Ib, resembles Ia, but has a short cranial polar branch, with the emission of segmental branches directly from the renal artery; pattern II, similar to Ib, but the caudal polar branch gives a branch that irrigates the cranial pole; in pattern III there are multiple renal arteries. The most frequent pattern, as in this study, is the Ia, detected in 77–97% 4 , 16 .…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“… 16 in the following types: pattern Ia, with the division of the renal artery into cranial and caudal polar branches, which branch into anterior and posterior segmental branches; pattern Ib, resembles Ia, but has a short cranial polar branch, with the emission of segmental branches directly from the renal artery; pattern II, similar to Ib, but the caudal polar branch gives a branch that irrigates the cranial pole; in pattern III there are multiple renal arteries. The most frequent pattern, as in this study, is the Ia, detected in 77–97% 4 , 16 .…”
Section: Discussionsupporting
confidence: 81%
“…The results showed that, as in humans, swine renal vascularization is provided by a single renal artery 4 . Although anatomical variations may occur from 30 to 40% in humans, being the accessory polar renal artery the most frequently observed 30 , such variations are rarely observed in pigs (1.7%) 4 and were not detected in this study.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations